2015
DOI: 10.1002/2327-6924.12215
|View full text |Cite
|
Sign up to set email alerts
|

Health consequences of adverse childhood experiences: A systematic review

Abstract: Purpose Adverse childhood experiences (ACEs) have been associated with negative health outcomes, but the evidence has had limited application in primary care practice. The purpose of this study was to systematically review the research on associations between ACEs and adult health outcomes to inform nurse practitioners (NPs) in primary care practice. Data sources The databases PubMed, CINAHL, PsycINFO, and Social Abstracts were searched for articles published in English between 2008 and 2013 using the search t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
321
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 505 publications
(355 citation statements)
references
References 51 publications
12
321
1
3
Order By: Relevance
“…A Level II systematic review of health consequences of ACE provided evidence for the necessity of screening for ACE in the primary care setting (Kalmakis & Chandler, 2015). Based on the work of Kalmakis and Chandler (2016), two pilot translational research studies demonstrated the impact of ACE on primary care patients, contributing additional evidence for the necessity of screening for ACE to reduce negative health consequences in the primary care setting (Aponte, 2017, Kalmakis, et al, 2018, & Shafer, 2017.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A Level II systematic review of health consequences of ACE provided evidence for the necessity of screening for ACE in the primary care setting (Kalmakis & Chandler, 2015). Based on the work of Kalmakis and Chandler (2016), two pilot translational research studies demonstrated the impact of ACE on primary care patients, contributing additional evidence for the necessity of screening for ACE to reduce negative health consequences in the primary care setting (Aponte, 2017, Kalmakis, et al, 2018, & Shafer, 2017.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the purpose of this translational research project is to incorporate evidence-based guidelines for Trauma-Informed Care (TIC) and screening for individuals presenting for SUD treatment (SAMHSA, 2014). The goal of this project is to translate research evidence through screening with a three part interview tool among clients receiving treatment for SUD in a IOP (Kalmakis & Chandler, 2015). This will be accomplished through utilization of the ACE screening tool used in previous studies, to facilitate patient-provider collaboration through compassion, trust, and motivation for change (Kalmakis, Schafer, Chandler, Aponte, & Roberts, 2018).…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Substance abusing parents can frequently be neglectful, abusive, unreliable, and emotionally unavailable for their children (Chassin, Rogosch, & Barrera, 1991; Velleman, Templeton, Reuber, Klein, & Moesgen, 2008). Children who are subjected to this kind of dysfunctional family situation, summarized in the concept of “Adverse Childhood Experiences” (ACE; Felitti et al, 1998), are at risk for developing problematic behaviours that affect both their own and their future children’s lives (Ivarsson, Saavedra, Granqvist, & Broberg, 2015; Kalmakis & Chandler, 2015; Lomanowska, Boivin, Hertzman, & Fleming, 2015). This study examines how individuals raised in such conditions reflect on their childhood and the kinds of difficulties that they have in their own role as a parent.…”
Section: Introductionmentioning
confidence: 99%
“…Experiencing child abuse and neglect has been associated with behavioural problems, long-lasting psychological disorders, obesity, low educational employment, criminal behaviour [16], lower perceived quality of life [17], intergenerational transmission [18] and even child death [19,20]. The negative outcomes of child abuse and neglect are also reflected in substantial costs in adulthood due to health service utilisation and productivity losses [21,22]. The high burden of abuse and neglect makes clear that efforts are needed to prevent and end child abuse and neglect.…”
mentioning
confidence: 99%